Potential of Trichoderma and AMF Mixture with Different Types of Fertiliser for Durio zibethinus Murray (Durian) and Artocarpus heterophyllus Lam. (Jackfruit) Growth - NELSON, JULIA; NOWEG, GABRIEL TONGA; JUSOH, ISMAIL (Borneo Journal of Resource Science and Technology, 2022)
Over the years, the co-inoculation of Trichoderma and arbuscular mycorrhizal fungi (AMF) with different types of fertiliser in a field condition has been understudied. This study explores the potential of Trichoderma and AMF mixture (T-AMF) with different types of fertiliser for plant growth with the objectives to: (i) analyse the growth of Durio zibethinus and Artocarpus heterophyllus fertilised with different types of fertiliser and inoculated with T-AMF and (ii) determine the optimal combination of organic and chemical fertiliser with T-AMF. A randomized complete block design was applied using seven treatments namely, 50 g organic fertiliser (OF) + T-AMF, 100 g OF + T-AMF, 50 g chemical fertiliser (CF) + T-AMF, 100 g CF + T-AMF, 100 g OF, 100 g CF, and control (without fertiliser and T-AMF). The growth analysis of D. zibethinus showed the highest mean height was at 100 g OF with T-AMF, stem diameter at 100 g CF with T-AMF, and the number of leaves at 50 g CF with T-AMF. For A. heterophyllus, the highest mean height and stem diameter was at 50 g OF with T-AMF and the number of leaves at 100 g OF with T-AMF. The optimal combination of fertiliser with T-AMF for D. zibethinus’ height was 100 g OF and number of leaves was 50 g CF. The optimal combination of fertiliser with T-AMF for A. heterophyllus’ height and stem diameter was 50 g OF. The optimal combination for its number of leaves was 100 g OF with T-AMF. This concludes that the application of fertiliser with T-AMF reacted differently to plant species and their growth parameters. The co-inoculation of Trichoderma and AMF may present a cheaper and sustainable alternative, especially when the planting scale is huge.